Os benefícios fiscais na proteção do meio ambiente - Moura, Beatriz Toledo de Moraes e (2023)
The present work deals with the role of certain tax benefits in protecting the environment, especially demonstrating the social function arising from extrafiscality which, through public policies from the Government, encourages and discourages society’s behavior, among which, the efforts for environmental preservation measures. From the above, it is demonstrated how tax extrafiscality has important and constitutionally enshrined values and its coexistence with the tax principles of contributory capacity, isonomy and tax legality. The extrafiscality, for the protection of habitation and subsistence of living beings, induces or discourages behaviours in the community, having its application limits within the national tax system, arranged with greater emphasis in the Fiscal Responsibility Law. However, if the budget limits are observed, due to tax benefits, there is no need to create a new environmental tax type, a “environmental tax”, going in accordance with the climate conferences that preach development in a conscious way and being in the pursuant to article 225 of CF/88. Practical environmental cases are observed with greater emphasis on federal tax incentives